Summer thermal behaviour of compact single family housing in a temperate climate in Argentina - Filippin, Maria Celina (2012)
This paper analyses the thermal-energy behaviour and the comfort/discomfort conditions in four compact massive housing located in a temperate climate in the central region of Argentina. The study has the following main objectives: (a) the thermal and energy monitoring of compact single family housing with the same technology, with different orientations, along the same period of summer 2010; (b) the statistical analysis of the indoor temperature behaviour, comfort conditions and electricity consumption for a historical period; and (c) the extrapolation of the results obtained in one of the studied dwellings to a sector of the neighbourhood. The analysis for summer showed that these houses would not reach indoor conditions of thermal comfort without using mechanical air conditioning. Monthly energy consumption average, summer consumption and February consumption for the historical period 2000–2009 were obtained. The average and a statistical analysis of the collected data revealed a normal distribution for the series. When monitoring results from 2010 were added to the statistical analysis, it was observed that the annual behaviour is similar to that of 2009 except for one of the houses in which the increase in consumption is the result of adding a split air conditioner. Extrapolation of results to houses in another block allowed us to infer – by analyzing electricity consumption patterns – that dwellers did not live in comfortable conditions. The addition of insulation on the roof was studied as a strategy to improve indoor conditions and reduce energy consumption. The cooling load, by assuming an indoor temperature of 25 °C, of a house with a thermally improved roof would reach energy savings of around 18%, figure that can be considered highly promising for a growing city.